“It’s Not Personal, It’s Business: or Teaching Structural Explanation” (at an HBCU) - Meyerson, Greg (Radical Teacher, 2015)
Needless to say, the dominant explanatory framework among our students generally is still individualism, and when it comes to their career trajectories, American dreams and equal opportunities predominate. Where I currently teach, the Historically Black University (HBCU) of civil rights fame North Carolina A and T University, it is more complicated.